Longitudinal [18F]FDG and [13N]NH3 PET/CT imaging of brain and spinal cord in a canine hemisection spinal cord injury model - Zhang Lijian; López-Picón Francisco R.; Jia Yingqin; Chen Yao; Li Juan; Han Chunlei; Zhuang Xiaoqing; Xia Hechun (Elsevier Inc., 2022)
To further understand the neurological changes induced by spinal cord injury (SCI) in its acute and subacute stages, we evaluated longitudinal changes in glucose and glutamate metabolism in the spinal cord and brain regions of a canine hemisection SCI model. [18F]FDG and [13N]NH3 positron-emission tomography (PET) with computed tomography (CT) was performed before SCI and at 1, 3, 7, 14, and 21 days after SCI. Spinal cord [18F]FDG uptake increased and peaked at 3 days post SCI. Similar changes were observed in the brain regions but were not statistically significant. Compared to the acute phase of SCI, [13N]NH3 uptake increased in the subacute stage and peaked at 7 days post SCI in all analyzed brain regions. But in spinal cord, no [13N]NH3 uptake was detected before SCI when the blood-spinal cord barrier (BSCB) was intact, then gradually increased when the BSCB was damaged after SCI. [13N]NH3 uptake was significantly correlated with plasma levels of the BSCB disruption marker, monocyte chemoattractant protein-1 (MCP-1). Overall, we showed that SCI induced in vivo changes in glucose uptake in both the spinal cord and the examined brain regions, and changes in glutamine synthetase activity in the latter. Moreover, our results suggest that [13N]NH3 PET may serve as a potential method for assessing BSCB permeability in vivo.